Pengembangan Script Instalasi dan Konfigurasi Samba Server pada OpenWrt 12.09 Attitude Adjustment - Didik Kurniawan; Imam Gunaro; Wisnu Wardhana (Jurnal Komputasi, 2014)
Samba is a re-implementation of the SMB (Server Message Block) / CIFS (Common Internet File System) from Windows NT used for providing shared access to files, printers and miscellaneous communications between nodes on a network. Samba uses the client- server mechanism whereby a computer will act as a server and should always be active to provide services to users. As an alternative, wireless router is used to replace computer server functionality to provide the same services as computer server did. By using OpenWrt, wireless router can be installed with Samba server. To simplify the installation and configuration process of Samba server, we designed a Bash shell script to automatically installing and configuring Samba server on OpenWrt router.Keywords: bash, networking, OpenWrt, router, samba, shell script